Vocational behavior of students from the counseling career at the University of Costa Rica - Alvarado Cordero, Silvia (2023)
The results of a 2020 study registered with the Institute of Educational Research (INIE, for the Spanish acronym) are presented. The general objective was to analyze the vocational behavior of students in the Counseling major at the University of Costa Rica between 2017 and 2019. A mixed research approach was applied with a predominance of a qualitative and phenomenological method. From a quantitative perspective, a questionnaire was given to 132 participating students from all levels of the major. Qualitative data was gathered through student focus groups. Results showed that when choosing their major, participating students relied on awareness of their own interests and skills. Initially they were unsure of their vocational goals, but they recognized their interest in entering university and pursuing a major related to human development. Students reported that it fit their personality and that since high school they had thought of a career that would allow them to help others. In addition, they emphasized the importance of their career guidance experiences in high school and university. The study showed students’ satisfaction with the choice of the Counseling major because it favored their personal development and the possibility of working with different populations. The study demonstrated the importance of strengthening career guidance education in high school and first years of university so that students can deepen their knowledge of themselves, their interests, skills, and educational opportunities. Furthermore, it is suggested that spaces be created to increase awareness in the student population of the Counseling major.